Proper INM enhances kachri yield - Jatav, M K; Balai, Roop Chand; Meena, Anita; Sharma, B D (Indian Horticulture, 2019)
Under hot arid agroclimate where soil is low in organic matter and available plant nutrients are of great importance in increasing yield by the balanced plant nutrients supply. The combined application of 50% recommended dose of NPK (40 kg N + 20 kg of P2O2 + 20 K2O) along with 15 t/ha FYM (in channel or in line where seed is grown) give higher yield (113.08 q/ha). Besides more yield, this combination also showed increasing efficiency, net return and B:C ratio. At this proportion inorganic sources maintained the availability of nutrients at a rate at which crop did not suffer stress. At the same time organic sources maintained the balance nutrition to crop for a longer duration. This proportion also favoured mineralization of organic source at desirable rate to maintain supply of nutrients to kachri crop.